Endarterectomy for symptomatic carotid stenosis in relation to clinical subgroups and timing of surgery. - Rothwell, P; Eliasziw, M; Gutnikov, SA; Warlow, C; Barnett, H (2004)
BACKGROUND: Carotid endarterectomy reduces the risk of stroke in patients with recently symptomatic stenosis. Benefit depends on the degree of stenosis, and we aimed to see whether it might also depend on other clinical and angiographic characteristics, and on the timing of surgery. METHODS: We analysed pooled data from the European Carotid Surgery Trial and North American Symptomatic Carotid Endarterectomy Trial. The risk of ipsilateral ischaemic stroke for patients on medical treatment, the perioperative risk of stroke and death, and the overall benefit from surgery were determined in relation to seven predefined and seven post hoc subgroups. RESULTS: 5893 patients with 33000 patient-years of follow-up were analysed. Sex (p=0.003), age (p=0.03), and time from the last symptomatic event to randomisation (p=0.009) modified the effectiveness of surgery. Benefit from surgery was greatest in men, patients aged 75 years or older, and those randomised within 2 weeks after their last ischaemic event, and fell rapidly with increasing delay. For patients with 50% or higher stenosis, the number of patients needed to undergo surgery (ie, number needed to treat) to prevent one ipsilateral stroke in 5 years was nine for men versus 36 for women, five for age 75 years or older versus 18 for younger than 65 years, and five for those randomised within 2 weeks after their last ischaemic event, versus 125 for patients randomised after more than 12 weeks. These results were consistent across the individual trials. INTERPRETATION: Benefit from endarterectomy depends not only on the degree of carotid stenosis, but also on several other clinical characteristics such as delay to surgery after the presenting event. Ideally, the procedure should be done within 2 weeks of the patient's last symptoms.